Z-axis Based Visualization of Map Elements - Cartographic Experiences with 3D Monitors Using Lenticular Foil Technology. (1st August 2013) - Bröhmer, Kai; Knust, Claudia; Dickmann, Frank; Buchroithner, Manfred F
Abstract : The current advent of autostereoscopic monitors and TV screens using lenticular foil technology proves the increasing desire to visualize movies, pictures, graphics or even maps in true-3D. These techniques could expand the cartographic 'tool box' drastically, implying that 3D is no longer limited to the well-known representation of landform characteristics. Major map design aspects of multi-image models have been analyzed and evaluated regarding their use in thematic cartography. For map design using lenticular foil technology empirical findings are necessary to position layers adequately along the z-axis of a 3D depiction. Hovering layers may generate additional information values, which seem to be able to compensate the shortcomings in 2D maps. Several parameters or dimensions of cartographic contents can be displayed simultaneously. True-3D display techniques must be implemented in a differentiated manner to achieve positive impacts on cartographic communication. However, lenticular foil technique opens perspectives for more diverse products in thematic cartography.